Perinatal hypoxic-ischemic damage: review of the current treatment possibilities - Frajewicki, A; Laštůvka, Z; Borbélyová, V; Khan, S; Jandová, K; Janišová, K; Otáhal, J; Mysliveček, J; Riljak, V (Physiological research, 2020)
Neonatal hypoxic-ischemic encephalopathy is a disorder with heterogeneous manifestation due to asphyxia during perinatal period. It affects approximately 3-12 children per 1000 live births and cause death of 1 million neonates worldwide per year. Besides, motor disabilities, seizures, impaired muscle tone and epilepsy are few of the consequences of hypoxic-ischemic encephalopathy. Despite an extensive research effort regarding various treatment strategies, therapeutic hypothermia with intensive care unit supportive treatment remains the only approved method for neonates who have suffered from moderate to severe hypoxic-ischemic encephalopathy. However, these protocols are only partially effective given that many infants still suffer from severe brain damage. Thus, further research to systematically test promising neuroprotective treatments in combination with hypothermia is essential. In this review, we discussed the pathophysiology of hypoxic-ischemic encephalopathy and delved into different promising treatment modalities, such as melatonin and erythropoietin. However, preclinical studies and clinical trials are still needed to further elucidate the mechanisms of action of these modalities.
Keywords: hypoxie; novorozenec; mozková hypoxie a ischemie; těhotenství; Female; Central Nervous System Depressants; Infant, Newborn; látky tlumící činnost CNS; Humans; ženské pohlaví; Pregnancy; Hypoxia; lidé; Erythropoietin; erythropoetin; Hypoxia-Ischemia, Brain; melatonin; Melatonin